Pastoral as an antithesis of apocalypse in Margaret Atwood’s The Year of the Flood - Jujar Singh, Hardev Kaur; Yahya, Amani Akram (International Journal of Special Education, 2022)
This article examines Margaret Atwood’s The Year of the Flood(2009) in the light of eco-criticism. The study focuses on apocalypse and pastoral depicted in the novel. On the one hand, the novel parades severe scenes of apocalyptic visions concerning the demise of environmental nature. On the other hand, it deals the pastoral landscapes representing the pure serenity of nature. Accordingly, there is a discrepant relationship between apocalypse and pastoral environmental categories in the course of the plot. Therefore, the study tackles Atwood’s futuristic conceptualization of apocalypse which threatens the ideal nature and the possibility of avoiding it through pastoral. That is, pastoral aspects represent the optimal natural topography; while imminent apocalypse endangers its unique continuation. In this case, the study attempts to explore pastoral as a remedy for looming environmental calamity. The concept of pastoral will be used as an antithesis of apocalypse in order to identify Atwood’s dissatisfaction with contemporary negative practices against environmental nature. By analyzing the contradiction between pastoral and apocalypse, I argue that regulatory ecological frameworks may exacerbate environmental awareness concerns by incentivizing readers and scholars to prioritize justification for their understanding the novel and avoiding misconception of nature through meaningfully engaging with natural circumferences. This finding leads me to call for more engagement with serious orientation toward community-led processes as a corrective to current non-regulatory systems regarding the decline of nature. Thus, this article expands on extant work in environmental communication by more thoroughly investigating the flaws in extant regulatory ecological frameworks and calling for a perspectival shift in environmental enlightenment.